Biologische Überwachung der Fischbestände bis ins Barentsmeer - Reinsch, H.H. (1975)
181. (63.) Forschungsreise des FFS "Anton Dohrn" in das Nordost-Gebiet Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010